The Neotropical Zethus biglumis species-group (Hymenoptera, Vespidae, Zethinae): description of three new species, with notes on the evolution of the group - Lopes, Rogério Botion; Hermes, Marcel Gustavo (Zootaxa, 2025)
With approximately 300 species, Zethus is the most speciose genus within the Vespidae. In a past phylogenetic study, Z. rugosiceps Fox was in the center of a discussion about the transition between two species-groups. However, the specimen used as basis was misidentified. Herein this specimen is described as a new species, Zethus nolli Lopes, sp. nov., and other two new, closely related species, Z. acromion Lopes, sp. nov. and Z. coracoides Lopes & Hermes, sp. nov., are also described. A key to the species of the biglumis group closely related to Z. rugosiceps is given and finally a brief reinterpretation of the evolutionary transition between the Z. biglumis and Z. clypearis species groups is provided.